EFFECTIVE STRATEGIES FOR MAINTAINING MOTIVATION - Koyshekenova, T.; Tajetdinova, A. (SCIENCE and SOCIETY, 2016)
This article is about effective ways of maintaining students‘ motivation in teaching English. The author of the article emphasize, that teachers should integrate the motivational strategies in their classrooms and help their pupils make the most of their language learning.
Keywords: motivation; true and clear aim; to create harmony; pair work; group work; role play; audio-visual materials; error correction